Functional screening identifies CRLF2 in precursor B-cell acute lymphoblastic leukemia - Yoda, Akinori (National Academy of Sciences, 2009)
The prognosis for adults with precursor B-cell acute lymphoblastic leukemia (B-ALL) remains poor, in part from a lack of therapeutic targets. We identified the type I cytokine receptor subunit CRLF2 in a functional screen for B-ALL–derived mRNA transcripts that can substitute for IL3 signaling. We demonstrate that CRLF2 is overexpressed in approximately 15% of adult and high-risk pediatric B-ALL that lack MLL, TCF3, TEL, and BCR/ABL rearrangements, but not in B-ALL with these rearrangements or other lymphoid malignancies. CRLF2 overexpression can result from translocation with the IGH locus or intrachromosomal deletion and is associated with poor outcome. CRLF2 overexpressing B-ALLs share a transcriptional signature that significantly overlaps with a BCR/ABL signature, and is enriched for genes involved in cytokine receptor and JAK-STAT signaling. In a subset of cases, CRLF2 harbors a Phe232Cys gain-of-function mutation that promotes constitutive dimerization and cytokine independent growth. A mutually exclusive subset harbors activating mutations in JAK2. In fact, all 22 B-ALLs with mutant JAK2 that we analyzed overexpress CRLF2, distinguishing CRLF2 as the key scaffold for mutant JAK2 signaling in B-ALL. Expression of WT CRLF2 with mutant JAK2 also promotes cytokine independent growth that, unlike CRLF2 Phe232Cys or ligand-induced signaling by WT CRLF2, is accompanied by JAK2 phosphorylation. Finally, cells dependent on CRLF2 signaling are sensitive to small molecule inhibitors of either JAKs or protein kinase C family kinases. Together, these findings implicate CRLF2 as an important factor in B-ALL with diagnostic, prognostic, and therapeutic implications.